PENERAPAN DESIGN THINKING DALAM OPTIMALISASI CUSTOMER JOURNEY DI OKE GARDEN - Nadya Kamilia Faiqoh,; Jasmine Chiquita Brilliana,; Melati Sukma Dewi,; Asty Dwinanda Putri,; Asep Taryana, (Jurnal Visionida, 2024)
This study aims to optimize the customer journey at OKE Garden using a Design Thinking approach. The primary issue faced by the company is a decline in revenue in 2024, despite undergoing digital transformation through a website. The approach taken so far has predominantly focused on digitalization without adequately addressing customer needs and challenges throughout their journey. This indicates that the customer journey has not been optimized to deliver a satisfactory experience. The study employs the five stages of Design Thinking (empathize, define, ideate, prototype, and test) to analyze and map the customer journey using Customer Journey Mapping (CJM). The novelty of this research lies in the application of Design Thinking to analyze the customer journey at OKE Garden, providing new insights into customer experience management in the retail sector. The use of Customer Journey Mapping facilitates a more in-depth identification of issues, including ineffective communication, limited design options, and challenges in the installation process and after-sales services. The findings suggest that website optimization, improved coordination, expanded design options, and enhanced after-sales services are necessary to increase customer satisfaction. With these improvements, OKE Garden is expected to enhance service quality, customer satisfaction, and competitiveness in an increasingly competitive market.